PERPUSTAKAAN KOTA PONTIANAK - Rijaluddin, Rijaluddin; Affrilyno, Affrilyno; Caesariadi, Tri Wibowo (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2020)
Reported by the Ministry of Education and Culture in 2019 regarding the literacy culture of each region, West Kalimantan is listed as the third lowest province in literacy culture or reading interest, the Pontianak City Government has provided places for the public to develop reading interest in the Pontianak City Library, however The Pontianak City Library as the parent of literacy media in Pontianak City has problems in terms of architecture such as inaccurate spatial programs, inadequate spatial size, and the formation of a library that is less representative. Several steps are used in the new library design starting from ideas, data, analysis, synthesis of the initial design to design development, the focus of library design is on programming a space where one of the commercial rooms and a separate room, also in library collections requires special treatment so that processing The collection provides space in the manager building by bridges between buildings for manager access. The new library design approach is adapted to current times by utilizing the latest technology related to libraries such as automatic lending and book creation tools, the library formation is also designed more iconically, on the main building facade of the library which adapts from the tanjak formation and applies secondary skin formations in the form of motifs, gill patterns typical of Pontianak City.